2018
DOI: 10.1371/journal.pone.0193276
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the inflammatory cells response to biodegradable Mg-based alloy extract

Abstract: Biodegradable Mg-based alloys have shown great potential as bone fixation devices or vascular stents. As implant biomaterials, the foreign body reaction (FBR) is an important issue to be studied, where the inflammatory cells play a key role. Here, we used two inflammatory cell lines i.e. THP-1 cells and THP-1 macrophages, to evaluate the effect of Mg–Nd–Zn–Zr alloy (denoted as JDBM) extracts on cell viability, death modes, cell cycle, phagocytosis, differentiation, migration and inflammatory response. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…To investigate the influence of the bare and PCL-based coated AZ31 Mg alloy on the immune response, the cellular model was represented by the monocyte/macrophage cell line RAW 264.7. In the specialised literature, studies reported the use of the human monocytic cell line THP-1 [ 99 , 100 , 101 , 102 , 103 ]. However, the mouse RAW 264.7 cell line, regardless of its transformed phenotype, is generally used in inflammation studies due to its response to Escherichia coli LPS which can imitate bacterial stimuli [ 98 , 104 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the influence of the bare and PCL-based coated AZ31 Mg alloy on the immune response, the cellular model was represented by the monocyte/macrophage cell line RAW 264.7. In the specialised literature, studies reported the use of the human monocytic cell line THP-1 [ 99 , 100 , 101 , 102 , 103 ]. However, the mouse RAW 264.7 cell line, regardless of its transformed phenotype, is generally used in inflammation studies due to its response to Escherichia coli LPS which can imitate bacterial stimuli [ 98 , 104 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the data available in literature regarding the influence of Zn on the inflammatory cytokine production is highly contradictory [ 165 ]. Additionally, Jin et al [ 100 ] reported that high concentrations of degradation products released in the culture media promoted the TNF-α expression, mainly due to the early foreign body response (FBR) process. Moreover, Ralston et al [ 166 ] reported that high levels of IL-1 are associated with low concentrations of NO, therefore justifying our findings regarding the high levels of this mediator induced by the extracts of the developed Mg-based materials, which correspond to lower levels of NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the literature utilising qPCR measure only a select few markers of immune cell activation [47]. For example, Jin et al (2018) showed that THP-1 macrophages produce lower amounts of pro-inflammatory TNFα after culture with higher concentrations of magnesium alloys, hence creating interest in the use of biodegradable Mg-based alloys in bone fixation devices or vascular stents [48]. Romero–Gavilan et al (2019) also showed that incorporating strontium coatings into sol-gel biomaterials increases TGFβ expression from a murine macrophage cell line, whilst decreasing TNFα expression.…”
Section: In Vitro Immunogenic Evaluationmentioning
confidence: 99%
“…Wang et al recommended that a minimum of six times to a maximum of 10 times dilution of extract was appropriate to be used in in vitro tests because the dilution would not result in cytotoxicity (31). Additionally, in our previous study, we found that 10–20% extract of JDBM could inhibit LPS-induced inflammation (32). Therefore, to explore possible anti-inflammatory effects, the extract was further diluted into 15% extract with cell culture medium as the experiment group (extract).…”
Section: Methodsmentioning
confidence: 85%
“…Evidence has shown that overrated magnesium would impair cell viability (46, 47). Our previous study also showed that above 50%, extract would result in cytotoxicity of macrophages, and this was partly the reason for anti-inflammation effects of the Mg-based alloy; besides, 20% extract could trigger inflammatory response without LPS stimulation owing to possible high osmotic pressure, although it was also able to inhibit inflammation after LPS stimulation (32). Therefore, it was reasonable to describe why JDBM inhibited inflammation “better” than 15% extract, and the reason why we selected 15% extract in our study was it will not trigger inflammation but has anti-inflammation effects after LPS stimulation, which offered a suitable dilution time of extract in the future research.…”
Section: Discussionmentioning
confidence: 97%